Task forms understand the integral concepts based on bloom's taxonomy theory - L Misu; Hasnawati Hasnawati (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
The purpose of this paper is to produce a task in understanding the concept of integral based on Bloom's Taxonomy theory. Understanding the concept according to Bloom's Taxonomy theory consists of seven categories: Interpreting, Modeling, Classifying, Summarizing, Concluding, and Explaining. This assignment has 7 questions each containing the concept of infinite integral and certain integral concepts. This task was tested legibility by two students and validated by 3 mathematics education experts. The results of the task readability test to understand the concept of Integral is good. The result of the task validation test is feasible to be used to track students' understanding in understanding the integral concept. The result of the content validation test on the students' understanding of the task of understanding the Integral Concept is good.